THE PRIVACY, TRUST, AND CUSTOMER EXPERIENCE AS KEY DRIVERS OF ONLINE PURCHASE DECISIONS: EVIDENCE FROM SHOPEE USERS IN BANDA ACEH - Mahyuddin (Gabungan Riset Edukasi dan Ekplorasi Teori (GREET), 2026)
This study aims to analyze the influence of privacy, trust, and experience on purchasing decisions through the Shopee platform in Banda Aceh City. The rapid growth of e-commerce requires a deeper understanding of the factors influencing consumer behavior in online transactions. This research employs a quantitative approach using a survey method targeting Shopee consumers in Banda Aceh City. The sampling technique applied was purposive sampling, with respondents selected based on their prior purchasing experience on Shopee. Data were analyzed using multiple linear regression to examine both partial and simultaneous effects among variables. The results indicate that privacy, trust, and experience have a positive and significant influence on purchasing decisions. Simultaneously, these three variables contribute significantly to enhancing consumer purchasing decisions. These findings suggest that personal data protection, the level of trust in the platform, and positive shopping experiences are crucial factors in encouraging consumer purchasing decisions through Shopee in Banda Aceh City